The Water & Conflict Podcast, with CGIAR - Episode 2 - International Water Management Institute (International Water Management Institute, 2024)
Hosts Christine Akume David and Bunmi Afolabi chat with photovoice participants Rahab Jasini, teacher in Adamawa State, and John T. Gadzama, an Adamawa State #IDP Leader, about the water challenges faced by their communities and the impact of the photovoice project.